The Causal Effect of Education on Climate Literacy and Pro-Environmental Behaviours: Evidence from a Nationwide Natural Experiment - Nattavudh Powdthavee (Institute of Labor Economics (IZA), 2020)
There is a widespread belief that a lack of education is the primary cause of public apathy to climate change. Yet, despite the global campaign to promote education as a tool to combat global warming, empirical evidence on the causal effect of education on climate literacy and pro-environmental behaviours remains worryingly scarce. Using the raising of the minimum school leaving age law in England from 15 to 16 years of age in September 1972 as a natural experiment, I showed that remaining in school as a result of the reform causally increased the level of comprehension about the causes of climate change. However, I found little causal evidence that more education also improved the pro-environmental behaviours of those who were affected by the reform. This raises an important question of whether policies aimed at improving climate change awareness through education can effectively produce long-lasting changes in pro-environmental behaviours.
Keywords: I26; Q54; 330; climate change; education; pro-environmental behaviours; regression discontinuity; UK